Recovery after volleyball: a narrative review - Closs, B.; Burkett, C.; Trojan, J. D.; Brown, S. M.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2020)
Volleyball is a popular sport, but there has been little research to date investigating the recovery process. Volleyball involves short bouts of high intensity exertion, often with limited time to rest between matches. This literature review highlights the specific methods used to recover after playing volleyball and evaluates their effectiveness. Recovery strategies have been shown to increase performance and prevent injury. Specific techniques identified include nutritional strategies, proper sleep, mental and psychological techniques, cold water immersion, and laser therapy. Some, such as nutrition and sleep, have been definitively shown to benefit volleyball players, while others, such as cold water immersion and laser therapy, have shown promise but require further research to determine their overall effect. Other areas of future research include evaluating the effectiveness of combined recovery techniques as well as determining which are best for rapid recovery.